Research Trends of Problem Based Learning (PBL) Based E-Modules to Improve Students' Science Process Skills in Science Learning: Bibliometric Analysis (2015-2024) - Sulhiyah, Sulhiyah (International Journal of Science Education and Science, 2025)
Improving science process skills is one of the important focuses in 21st century science education. One effective method is the use of e-modules based on Problem Based Learning (PBL) that can help students develop these skills. This study aims to review research trends related to the use of PBL-based e-modules in improving students' science process skills in the period 2015 to 2024. This research method uses a descriptive and analytical approach with data obtained from scientific publications indexed by Google Scholar, using tools such as Publish or Perish and Dimension.ai. The analysis process is carried out based on PRISMA guidelines to filter and assess the quality of documents. The collected data was analyzed using a bibliometric approach with the help of VOSviewer software to map the main keywords. The results showed that the research trend related to PBL-based e-modules experienced a significant increase from 2015 to 2023, but slightly decreased in 2024. Scientific articles became the most dominant type of publication, indicating a high interest in the use of PBL-based e-modules. Some of the keywords that frequently appear are “problem solving ability,” “STEM approach,” and “critical thinking skill,” indicating the main focus on the development of critical thinking skills and the integration of the STEM approach. This research provides a comprehensive overview of the development of PBL-based e-module research trends in science learning, as well as identifying further development opportunities such as the integration of local wisdom and technology to improve students' science process skills.